FAKTOR PENYEBAB KETERLAMBATAN PEKERJAAN KONSTRUKSI MENURUT PRESEPSI KONTRAKTOR - Elvira Handayani (Universitas Batanghari, 2016)
Jambi city is one of the cities that began to develop on the island of Sumatra in the field of infrastructure and the economy, so development is one activity that is enhanced by the local government in the framework of the welfare and prosperity of the people of Jambi. In the process of development is very common problems causing delays in work, many factors causing delays become very common problem faced by the parties involved, especially the Contractor which act as implementers.From the research the factors causing delays in construction work in the city of Jambi as perceived by the contractor, a number of conclusions, among others:Factors Materials and Materials obtain a total score of 7.18,Environmental Factors obtain a total score of 5.96,Financial Factor obtain a total score of 5.99,Factors Changes obtain a total score of 6.95,The Labor get highest total score is 7.29,Factors and Control Time to get a total score of 5.93,Factors Hardware obtain a total score of 7.15